2021
DOI: 10.1080/19475705.2021.1910351
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale approach to analyse the evolution of soft rock coastal cliffs and role of controlling factors: a case study in South-Eastern Italy

Abstract: The evolution of soft rock coastlines is strictly related to natural and anthropogenic conditions, which in some cases can determine also an acceleration of coastal retreat. The recent evolution of a soft rocky coastal stretch on the Italian southern Adriatic sector is analysed. To investigate the most important contributing factors to coastal evolution, a detailed multi-temporal (1954-2017) morphological analysis with photo-interpretation is carried out, which allows gaining a general understanding of the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In the close locality of Torre la Punta (1 km far from Punta Caleo), a retreat rate of 0.8 m/yr was assessed, showing how the rate of erosion can suddenly vary in the same coastal areas [8]. Regarding other cases in the Adriatic Sea, in Torre dell'Orso (Apulia region), the rate of erosion (in fine limestones) was found to be between 0.08 m/yr and 0.12 m/yr [71,86], while in the Abruzzo region (on the Pleistocene clay-sand-sandstone-conglomerate marine sequence), the retreat rate ranged between 0.15 m/yr and 1 m/yr [87]. In the area between Gabicce and Pesaro, a few kilometers northward of our case study (characterized by similar lithologies), a mean retreat rate of 0.16 m/yr was calculated in the last 6000 year [88].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the close locality of Torre la Punta (1 km far from Punta Caleo), a retreat rate of 0.8 m/yr was assessed, showing how the rate of erosion can suddenly vary in the same coastal areas [8]. Regarding other cases in the Adriatic Sea, in Torre dell'Orso (Apulia region), the rate of erosion (in fine limestones) was found to be between 0.08 m/yr and 0.12 m/yr [71,86], while in the Abruzzo region (on the Pleistocene clay-sand-sandstone-conglomerate marine sequence), the retreat rate ranged between 0.15 m/yr and 1 m/yr [87]. In the area between Gabicce and Pesaro, a few kilometers northward of our case study (characterized by similar lithologies), a mean retreat rate of 0.16 m/yr was calculated in the last 6000 year [88].…”
Section: Discussionmentioning
confidence: 97%
“…Although the DSAS tool was created to analyze the shoreline movements, its use in cliff-retreat studies is widely documented in the literature [69][70][71][72].…”
Section: Morphological Analysismentioning
confidence: 99%
“…Main Objective Exclusion Cause Dominey-Howes et al (2000) [98] process identification CBDs produced by tsunami [99] vulnerability study No CBD dynamics data are reported Andriani and Walsh (2007) [100] process identification No CBD dynamics data are reported Scicchitano et al (2010) [101] process identification No CBD dynamics data are reported Furlani et al (2011) [102] process identification No CBD dynamics data are reported Paris et al (2011) [2] review preface No CBD dynamics data are reported Mastronuzzi and Pignatelli (2012) [103] process identification CBDs produced by tsunami Katz and Mushkin (2013) [104] process identification No CBD dynamics data are reported Mottershead et al (2015) [105] process identification CBDs produced by tsunami Shah-Hosseini et al ( 2016) [106] hazards study No CBD dynamics data are reported Amores et al (2020) [107] storm simulation No CBD dynamics data are reported Ruban (2020) [3] virtual perspective No CBD dynamics data are reported Ferrando et al (2021) [108] process identification No CBD dynamics data are reported Fortelli et al (2021) [109] process identification No CBD dynamics data are reported Lollino et al (2021) [110] process identification No CBD dynamics data are reported…”
Section: Appendix Amentioning
confidence: 99%
“…Main Objective Exclusion Cause Dominey-Howes et al (2000) [98] process identification CBDs produced by tsunami [99] vulnerability study No CBD dynamics data are reported Andriani and Walsh (2007) [100] process identification No CBD dynamics data are reported Scicchitano et al (2010) [101] process identification No CBD dynamics data are reported Furlani et al (2011) [102] process identification No CBD dynamics data are reported Paris et al (2011) [2] review preface No CBD dynamics data are reported Mastronuzzi and Pignatelli (2012) [103] process identification CBDs produced by tsunami Katz and Mushkin (2013) [104] process identification No CBD dynamics data are reported Mottershead et al (2015) [105] process identification CBDs produced by tsunami Shah-Hosseini et al ( 2016) [106] hazards study No CBD dynamics data are reported Amores et al (2020) [107] storm simulation No CBD dynamics data are reported Ruban (2020) [3] virtual perspective No CBD dynamics data are reported Ferrando et al (2021) [108] process identification No CBD dynamics data are reported Fortelli et al (2021) [109] process identification No CBD dynamics data are reported Lollino et al (2021) [110] process identification No CBD dynamics data are reported…”
Section: Appendix Amentioning
confidence: 99%